A model for 'sustainable' US beef production. Issue 1 (January 2018) - Eshel, Gidon; Shepon, Alon; Shaket, Taga; Cotler, Brett; Gilutz, Stav; Giddings, Daniel; Raymo, Maureen; Milo, Ron
Abstract Food production dominates land, water and fertilizer use and is a greenhouse gas source. In the United States, beef production is the main agricultural resource user overall, as well as per kcal or g of protein. Here, we offer a possible, non-unique, definition of 'sustainable' beef as that subsisting exclusively on grass and by-products, and quantify its expected US production as a function of pastureland use. Assuming today's pastureland characteristics, all of the pastureland that US beef currently use can sustainably deliver ≈45% of current production. Rewilding this pastureland's less productive half (≈135 million ha) can still deliver ≈43% of current beef production. In all considered scenarios, the ≈32 million ha of high-quality cropland that beef currently use are reallocated for plant-based food production. These plant items deliver 2- to 20-fold more calories and protein than the replaced beef and increase the delivery of protective nutrients, but deliver no B12 . Increased deployment of rapid rotational grazing or grassland multi-purposing may increase beef production capacity. The US beef industry is regarded as environmentally unsustainable. Modelling a system where cattle subsist solely on grass and food industry by-products, the authors estimate that 45% of current production could be achieved without the use of any high quality cropland.